Readily available titania nanostructuring routines based on mobility and polarity controlled phase separation of an amphiphilic diblock copolymer. Issue 11 (5th March 2018) - Hohn, Nuri; Schlosser, Steffen J.; Bießmann, Lorenz; Grott, Sebastian; Xia, Senlin; Wang, Kun; Schwartzkopf, Matthias; Roth, Stephan V.; Müller-Buschbaum, Peter
Abstract : Diblock copolymer templating combined with sol–gel chemistry is a powerful tool to control the morphology of titania nanostructures. Abstract : The amphiphilic diblock copolymer polystyrene- block -polyethylene oxide is combined with sol–gel chemistry to control the structure formation of blade-coated foam-like titania thin films. The influence of evaporation time before immersion into a poor solvent bath and polarity of the poor solvent bath are studied. Resulting morphological changes are quantified by scanning electron microscopy (SEM) and grazing incidence small angle X-ray scattering (GISAXS) measurements. SEM images surface structures while GISAXS accesses inner film structures. Due to the correlation of evaporation time and mobility of the polymer template during the phase separation process, a decrease in the distances of neighboring titania nanostructures from 50 nm to 22 nm is achieved. Furthermore, through an increase of polarity of an immersion bath the energetic incompatibility of the hydrophobic block and the solvent can be enhanced, leading to an increase of titania nanostructure distances from 35 nm to 55 nm. Thus, a simple approach is presented to control titania nanostructure in foam-like films prepared via blade coating, which enables an easy upscaling of film preparation.